[Article sans titre] - Gagné, Jean-H. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1952)
SummaryThe arbitration awards studied in this issue are those rendered during the months of July, August, September, October and November, 1952. We are only reporting the awards containing comments which might be of particular interest to our readers.